3D printing of protein-based composite fruit and vegetable gel system. (April 2021) - Chen, Yangyang; Zhang, Min; Phuhongsung, Pattarapon
Abstract: The purpose of this research was to develop protein-based composite fruit and vegetable printing inks with good printability. The printing characteristics and sensory evaluation properties of five different animal and vegetable proteins as a matrix and fruit and vegetable powder composite printing ink were studied. Results showed that the ink based on peanut protein isolate exhibited the best printing characteristics. The extruded line diameter is 0.83 mm closest to the nozzle diameter, and the height change is only 0.3 mm within 120 min, which is significantly better than other protein inks and has high self-supporting and precision. Moreover, the peanut protein-based ink also scored 7.78 points in the sensory evaluation experiment, which was significantly higher than other protein inks. This showed that the ink based on peanut protein can be well accepted by consumers, which also makes the research more feasible and practical. In this research, the universality of peanut protein-based ink was tested. The results showed that for different fruit and vegetable powders, the composite fruit and vegetable ink based on peanut isolate protein has stable and better printing properties. This provides certain prerequisites for the development of different peanut protein isolate-based inks, and provides the possibility to solve the diversity of different nutrition customization problems and improves consumer acceptability. Highlights: Protein-enriched 3D printed samples were developed. Hawthorn powder added with peanut protein isolate has good 3D printing properties. Peanut protein ink with hawthorn powder was applicable to other fruit and vegetable inks. 3D printed protein-based samples could be customized for personalized nutrition.